Exploring anxiety symptoms in a large‐scale twin study of children with autism spectrum disorders, their co‐twins and controls. (30th July 2013) - Hallett, Victoria; Ronald, Angelica; Colvert, Emma; Ames, Catherine; Woodhouse, Emma; Lietz, Stephanie; Garnett, Tracy; Gillan, Nicola; Rijsdijk, Fruhling; Scahill, Lawrence; Bolton, Patrick; Happé, Francesca
<x xml:space="preserve">Abstract</x> Background Although many children with autism spectrum disorders (ASDs) experience difficulties with anxiety, the manifestation of these difficulties remains unresolved. The current study assessed anxiety in a large population‐based twin sample, aged 10–15 years. Phenotypic analyses were used to explore anxiety symptoms in children with ASDs, their unaffected co‐twins and a control sample. Methods Participants included 146 families from the Twins Early Development Study (TEDS) where one or both children had a suspected ASD. Eighty control families were also included. The Revised Child Anxiety and Depression scale (Chorpita, Yim, Moffitt, Umemoto & Francis, 2000) was completed (self‐ and parent‐report), along with diagnostic and cognitive tests. Children were categorized into four groups (a) ASD (b) Broader Autism Phenotype (BAP: mainly co‐twins of children with ASDs, with high subclinical autistic traits) (c) unaffected co‐twins (with neither ASDs nor BAP) (d) controls. Results Children in the ASD and BAP groups scored significantly higher than controls for all parent‐rated (although not child‐rated) anxiety subscales. There were no significant differences between the ASD and BAP groups for any of the parent‐rated anxiety subscales. Compared with controls, unaffected co‐twins showed significantly heightened Social Anxiety, Generalized Anxiety, and Panic symptoms. Significant associations were observed between certain anxiety subscales and both IQ and ASD symptoms. For example, greater parent‐rated Social Anxiety was associated with higher IQ and increased social and communicative impairments. Significant interrater correlations were observed for anxiety reports in children with ASDs (r = .27–.54; p < .01), their unaffected co‐twins (r = .32–.63; p < .01) and controls (r = .23–.43; p < .01) suggesting that children in this sample with and without ASD symptoms were able to report on their anxiety symptoms with some accuracy. Conclusions These findings support previous reports of heightened anxiety in children with ASDs, at least on parent‐reported measures. Unaffected co‐twins of children with ASDs also showed increased anxiety, generating questions about the potential etiological overlap between ASDs and anxiety. Progress in this area now depends on more refined anxiety measurement in ASDs and continued investigation of interrater differences.